Survei Minat dan Pengelolaan Ekstrakurikuler Bola Voli SMP-SMA Sederajat Se-Kecamatan Bojong 2019 (Universitas Negeri Semarang, 2021)
The purpose of this research is to describe the student interest and volleyball extracurricular management in Junior and Senior High School of Bojong District. This research uses qualitative methode. The data source for this research are primary and secondary. The primary data taken by observation and interview, meanwhile the secondry data taken by documentation. There are 120 interviewees. The research is condusted in five schools. The target of the research is junior and senior high schools in Bojong District. The data analysed used Mile and Huberman model (data reduction, data presentation, conclusion drawing). The results showed that the schools had run well extracurricular management and also the schools had not applied management in sports, especially volleyball extracurricular activities. The students’ interest in extracurricular activities was very good, it can be seen from the enthusiasm of students joining volleyball extracurricular activities at school. The conclution is management of volleyball extracurricular in junior and senior high schools was quite good. In the terms of ownership, the facilities that support volleyball extracurricular activities and the organizational structures were suitable with their respective roles. The students' interest in volleyball extracurricular activities was good, it was proven by their participating volleyball extracurricular activities without enforcement